2019
DOI: 10.1017/s0960428619000180
|View full text |Cite
|
Sign up to set email alerts
|

Out of the Frying Pan Into the Fire: The Community Structure of Epiphytes in Brazilian Savanna After the Passage of Fire

Abstract: Cerrado sensu stricto (a physiognomy of the Cerrado domain, the Brazilian savanna) is subject to the annual occurrence of fire. Data on the epiphytic community in this physiognomy is scarce, as is evaluation of the influence of fire on its structure and composition. The aim of this study was to describe the structure of the vascular epiphyte community and its relationships with phorophytes in the Cerrado domain, Southeast Region of Brazil, after the passage of fire. We found the greatest abundance of epiphytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…are repeatedly observed epiphytically in relatively dry forests in southern Mexico (Wolf, 2005), and in French Guiana, Mori et al (2002) observed two aroid species as accidental epiphytes. A considerable number of studies investigated assemblages of vascular epiphytes in southeastern Brazil along the Atlantic coast, where accidental epiphytes are an important part of the epiphytic flora (e.g., Alves & Neto, 2014; Couto et al, 2016; Couto et al, 2019, 2017; Furtado & Neto, 2015a, 2016; Menini Neto et al, 2020), especially in urban areas (Alvim et al, 2020, 2021; Furtado & Neto, 2015b). Among 35 cactus species observed epiphytically in Bolivia, Ibisch et al (2000) classified 14 as accidental.…”
Section: Global Occurrences Of Accidental Epiphytesmentioning
confidence: 99%
“…are repeatedly observed epiphytically in relatively dry forests in southern Mexico (Wolf, 2005), and in French Guiana, Mori et al (2002) observed two aroid species as accidental epiphytes. A considerable number of studies investigated assemblages of vascular epiphytes in southeastern Brazil along the Atlantic coast, where accidental epiphytes are an important part of the epiphytic flora (e.g., Alves & Neto, 2014; Couto et al, 2016; Couto et al, 2019, 2017; Furtado & Neto, 2015a, 2016; Menini Neto et al, 2020), especially in urban areas (Alvim et al, 2020, 2021; Furtado & Neto, 2015b). Among 35 cactus species observed epiphytically in Bolivia, Ibisch et al (2000) classified 14 as accidental.…”
Section: Global Occurrences Of Accidental Epiphytesmentioning
confidence: 99%
“…In Brazil, the knowledge of epiphytic flora is broader in the south and southeast regions (Menini Neto et al, 2020). In riparian forests of southern Brazil, studies on epiphytism have been conducted by Graeff et al (2018), Rocha-Uriartt et al (2016), Costa et al (2020) and Bonnet et al (2010;, in the state of Paraná.…”
Section: Introductionmentioning
confidence: 99%